'It doesn't really matter which university you attend or which subject you study while abroad.' the massification of student mobility programmes and its implications for equality in higher education. Issue 1 (2nd January 2018) - Courtois, Aline
ABSTRACT: Based on documentary analysis and interviews, the article examines the current practices of Irish universities in their efforts to increase their students' participation in international exchange programmes. It argues that increased participation, while a positive outcome, obscures a growing differentiation in the types of exchange programmes and destinations. This emerging stratification leads to differentiated experiences and outcomes, which may amplify other forms of stratification pervading the higher education sector. In particular, we look at the emergence of different models of exchange, that have moved away from an academic focus towards a more easily manageable model better suited to the massification underway. We suggest that Irish higher education institutions contribute to making credit mobility a space, where students can deploy socially unequal strategies and where the more vulnerable remain either excluded, or limited to 'second best' programmes, devalued academically or where pedagogic opportunities are lost. This is one of the manifestations of the production of internationalization under the pressures of cost-saving, corporatization and the employability discourse.